Ambiência do ponto de venda: antecedentes das emoções e significados para os consumidores - um estudo exploratório no setor farmacosmético - Geargeoura, Lucien Jacques (2010)
The design on the sales environment of a store is one of the key tools that retailers have available to obtain competitive advantages and improve their performance. This complex environment offers several stimuli that affect the clients' purchasing behavior. In their purchasing experience, clients guide themselves, among other factors, by their emotions and meaning aroused by these stimuli. This study has as objective to understand how emotions and meaning derived by the client from the sales environment result from different environmental elements that compose the sales environment of the store. Starting from the phenomena of perception, affection and cognition in the context of the sales environment, we reviewed the main studies on the environmental influence on consumers inside the store, focusing on their internal reactions, particularly on the emotions felt and on the meanings attributed to the store environment by customers. We detailed and organized the list of elements that build up the physical environment of store, using it as base for the analysis of the effects of these elements on customers, in terms of experienced emotions and meanings attributed clients to the store. Trying to understand how the sales environment of store connects with the emotions and meanings aroused by it, we performed an exploratory, qualitative, and more descriptive than explanatory research, using techniques such as the partially structured interview complemented by aspects of the in-depth interview, and the EmotiScape instrument. The results, as expected from an exploratory investigation, cover many aspects. In terms of empiric results, we identify the environment elements actually perceived by clients in the store, the main integration among such elements when being perceived, and the emotion and the meanings attributed to them by customers. We describe the main mechanisms the bind the perceived environmental elements to emotions and meanings attributed to the store environment. We also identify and describe examples of integrations between the affective and cognitive processes which result from environmental elements. As a first conceptual contribution of our research, we confirm the point of view presented by the contigencial models of perception from Psychology, that the store environment stimuli can be noticed 'one by one' or as whole, and also intermediary cases in which a certain number of stimuli act in concert as source of emotion and meanings for the customer. Straight from this fact result an important managerial implication: knowing in advance isolated or packaged stimuli and their potential associations to specific emotions and meanings, we can intentionally shape the point os sale to evoke (or avoid) emotional and cognitive effects on the customer, using the point of sale design as a tool for developing marketing strategies and attaining a desired level of performance for a store. The second conceptual contribution of our study is the validation, in the context of the sales environment, of an approach relatively recent in Psychology, which sees the affective and cognitive phenomena integrated in a larger and information processing scheme performed by the human brain. The results from this study the vision, showing that customers use their emotions to build reasoning and judgments concerning the store as, inversely, build reasoning that result in (on reinforce) their emotion regarding the store. Finally, the study also contributes in advances in the usage of innovative data collection instruments that can measure a diversified range of emotional states (the EmotiScape) and avoid verbal blockages from interview people when reposting perceived environmental stimuli (using collections of images detailing the store environment).